KARAKTERISTIK CURD BERBAHAN DASAR EKSTRAK KACANG HIJAU (Vigna radiata) dengan WHEY TAHU KEDELAI (Glycine max) SEBAGAI BAHAN PENGGUMPAL - Elygio, Yudhistira Denta; Legowo, Anang Mohamad; Al-Baarri*, Ahmad Ni’matullah (Universitas Sebelas Maret (UNS), 2016)
This research aims to determine the total rendement, moisture content, protein content, as well as curd texture from green beans by using soy whey as coagulant. The study was conducted using 1% citric acid and the variation of whey soybean with the concentration of 2, 4, 6, 8% (v/v). The use of whey tofu as a coagulant indicates the effect that causes increased total rendement, levels, protein content, and curd texture. The best treatment in this study was on the administration of 2% whey soybeans as coagulant. Treatment with 2% whey soybeans can be regarded as the best treatment because it has the best test results with the highest total yield, low water content, the highest protein content, and the highest texture of hardness. It can be said that making curd using whey tofu soy as a coagulant is a good thing to do.